GOLD’S ZAKAT NISHAB AS AN ALTERNATIVE TO THE MINIMUM WAGE STANDARD IN INDONESIA - Gumilar, Dedi (Jurnal Ekonomi dan Manajemen, 2024)
This article discusses the minimum wage setting standard based on the amount of gold zakat nishab compared to the determination of the minimum wage in Bandung City from 2016 to 2020. The emergence of protests and labor demonstrations at the time the minimum wage was set, indicates that the minimum wage has not provided a sense of justice. for the workers. This research was conducted to find a better alternative formulation for determining the minimum wage each year. The method used is a literature study and a comparative study between the minimum wage set by the government and the calculation of the proposed minimum wage. As a research sample, using data of Bandung City minimum wage from 2016 to 2020. Meanwhile, the gold price data used is Antam's spot gold price at the close of October from 2015 to 2019. The proposed minimum wage is the gold price per gram the year before, multiplied by the gold zakat nishab (85 grams), and the result is divided by 12 months. The calculation result shows that the proposed minimum wage compares to the minimum wage set annually is 47% higher on average. This research concludes that the gold zakat nishab can be used as the basis for determining the UMK because the price of gold during the research period was not affected by inflation.